Integrated analysis of gut and oral microbiome in men who have sex with men with HIV Infection - Li Shuang; Su Bin; Wu Hao; He Qiushui; Zhang Tong (ASM Press, 2025)
Human immunodeficiency virus (HIV) infection leads to severe deficiency in host immunity by depletion of CD4+ T-cells, resulting in an imbalance between the human microbiome and host immune response. Alterations in both gut and oral microbiomes have been observed in people living with HIV (PLWH). However, the impact of an altered gut and oral microbiome on HIV disease progression and the relationship between them in PLWH have not been explored. In this longitudinal study, we enrolled acute HIV-infected men who have sex with men (MSM) (n = 15), chronic HIV-infected MSM (n = 15), and HIV-uninfected MSM controls (n = 15). We collected anal and throat swab samples at recruitment (W0) from all participants and at 12 wk after antiretroviral therapy (ART) (W12) from the patients and performed 16S rRNA gene sequencing of genomic DNAs extracted from these swabs. In HIV-infected individuals with CD4 T-cell counts < 350 cells/µL, the increase in abundance of Streptococcus in the oral microbiome was inversely correlated with that of Streptococcus in the gut microbiome (r = −0.490, P = 0.039). In addition, the lower CD4+ T-cell counts (<200 cells/µL) were associated with the higher abundance of Escherichia–Shigella and the lower abundance of Methylobacterium–Methylorubrum of the gut microbiome in HIV-infected individuals. We demonstrate the alteration of gut microbiome resulting from HIV infection and ART and the relationship between the gut and oral microbiome in PLWH and controls. These findings highlight the need for a better understanding of the interactions between the oral and gut microbiome and its potential role in HIV disease progression.
IMPORTANCE
Our longitudinal integrated study has shown the marked alterations in the gut and oral microbiome resulting from acute and chronic HIV infection and from antiretroviral therapy. Importantly, the relationship between oral and gut microbiomes in people living with acute and chronic HIV infection and “healthy” controls has also been explored. These findings might contribute to a better understanding of the interactions between the oral and gut microbiomes and its potential role in HIV disease progression.